2017
DOI: 10.1111/1440-1681.12697
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin1 promotes carcinogenesis of glioma in vitro

Abstract: As the most prevalent and lethal type of brain tumours, gliomas, especially malignant ones, are relatively resistant to conventional therapies. Gremlin 1 (GREM1) is a secreted glycoprotein that is implicated in the maintenance of cancer stem cells in tumour hierarchy. In the current study, the role of GREM1 in the carcinogenesis of glioma was studied using a knockdown approach. We first examined the expression level of GREM1 in the clinical samples, and then evaluated the effect of GREM1 knockdown on the viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Importantly, proinflammatory genes and ECM-related genes also were elevated. Moreover, the GO enrichment analysis of these data emphasizes the role of wound healing as one of the biological processes implicated in Gremlin-mediated responses, which could be related to GREMLIN-induced phenotype transformations previously described in different cell types [7,[57][58][59][60][61]. Moreover, the ECM region and structural constituent are the main highlighted terms of cellular components and molecular function, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, proinflammatory genes and ECM-related genes also were elevated. Moreover, the GO enrichment analysis of these data emphasizes the role of wound healing as one of the biological processes implicated in Gremlin-mediated responses, which could be related to GREMLIN-induced phenotype transformations previously described in different cell types [7,[57][58][59][60][61]. Moreover, the ECM region and structural constituent are the main highlighted terms of cellular components and molecular function, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that mesenchymal stromal cell-derived GREM1 can promote EMT in human esophageal squamous cell carcinoma [37]. Knockdown of GREM1 also inhibits EMT and invasion of glioma cells [38].…”
Section: Introductionmentioning
confidence: 98%
“…GREM1 is also involved in the fibrosis of various organs, including lung [29][30][31], kidney [32][33][34], and pancreas [35]. Interestingly, EMT phenomenon induced by GREM1 is known to be important for organ fibrosis [36] and tumor promotion [37,38]. GREM1 activates EMT process and profibrotic phenotype in tubular epithelial cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…GREM1 is overexpressed and increases cell growth and proliferation in lung adenocarcinoma [30]. Furthermore, GREM1 promotes carcinogenesis of glioma in vitro [31,32].…”
Section: Introductionmentioning
confidence: 99%